Analysis of blood flow through stenosed artery with Einstein Viscosity - Bhandari, Bishnu Prasad; Kafle, Jeevan; Pokharel, Chudamani (BIBECHANA, 2024)
The presence of arterial stenosis significantly disrupts normal flow, posing heightened risks and exerting a greater impact on the cardiovascular system compared to other geometric abnormalities. The investigation of flow parameters in an artery with mild stenosis necessitates analyzing the varying viscosity of blood from the central core line to the vessel wall. This study employs the Navier-Stokes equation in cylindrical polar form to analyze fluid dynamics in axisymmetric directions, accounting for the effective viscosity of blood at radial distances (Einstein coefficient of blood viscosity). By solving this equation with appropriate boundary conditions, analytical expressions for the velocity profile, volumetric flow rate, pressure drop, wall shear stress, and the ratios of pressure drop and shear stress are obtained for the stenosed artery using the Einstein coefficient of blood viscosity. Additionally, variations in plasma viscosity and hematocrit are examined concerning these flow parameters in the stenosed artery region. These findings underscore the complexity of blood flow dynamics, emphasizing the critical importance of incorporating significant factors such as the Einstein coefficient of blood viscosity to advance our understanding of vascular physiology in the presence of stenosis.